PERSEPSI KONSUMEN TERHADAP PROSES PERSONAL SELLING DI PT TALENTS SPECTRUM CABANG DEPOK - ., Muhlis; ., Ruswanto (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2018)
Personal selling is used in product marketing of PT. Talents Spectrum which is a form of direct communication between sales people who represent companies and potential customers. The object of research is consumers who buy the services of PT. Talents Spectrum Depok Branch. The purpose of this study was to determine consumer perceptions of the approach process, presentation stage, handle objections and closing sales in personal selling. Samples were taken using Slovin formula and analyzed using the Weighted Means Score (WMS). The results of the study showed that the entire process of personal selling carried out by the company's sales force had very good assessment criteria, with a value of 4.043. The process stage that has the smallest value is the presentation stage, with a value of 4.031. The smallest indicator of personal selling is self-introduction to the approach process with 3,917 and reconfirming the product explanation in the sales closing process with a value of 3,917.